A NEW PARADIGM FOR COOPERATIVE SOCIETIES UNDER THE NEW BELGIAN CODE OF COMPANIES AND ASSOCIATIONS - Tilquin, Thierry; Delcorde, Julie-Anne; Bernaert, Maïka (International Journal of Cooperative Law, 2025)
The Belgian law on cooperative societies has been substantially modified following a broader reform of company law in 2019 and induces achange of paradigm: the legislator indeed took this opportunity to modify a regime of flexibility and “neutrality” in relation to the cooperative principles of the cooperative society form to limit said form to the companies wishing to follow the cooperative model and principles.